The incidence, management and outcomes of stage IIIB cervical cancer in a low- and middle-income setting - Dalvie, Zaeem (Division of Radiology, 2025)
Background: Cervical cancer is the second most common cancer in South Africa with stage III being the most common presenting stage. Hydronephrosis is a frequent complication in advanced disease and is associated with poorer outcomes. This review aims to evaluate the management and outcomes of patients with stage IIIB cervical cancer. Aim: To describe the incidence, treatment offered and outcomes in women with stage IIIB cervical cancer in a middle-income setting. It further aims to evaluate these differences in women with pelvic sidewall (PSW) involvement alone versus PSW with unilateral and bilateral hydronephrosis. Objectives: Determine the overall survival and disease-free survival of patients with stage IIIB cervical cancer with specific attention to those patients with hydronephrosis, determine the incidence of unilateral and bilateral hydronephrosis, determine how many patients with bilateral hydronephrosis were offered percutaneous nephrostomies, describe the treatment offered and outcomes of the women who were offered nephrostomies, describe the complications that arose by inserting nephrostomies, and to determine how many patients with hydronephrosis received concurrent chemoradiation. Methods: A retrospective audit was conducted to review clinical data of a cohort of patients who received treatment for stage IIIB cervical cancer at Groote Schuur Hospital between January 2017 and December 2018. The data collected included age, HIV status, comorbidities, pelvic sidewall involvement, hydronephrosis, treatment intent, treatment modalities, nephrostomy referral, treatment response and survival outcome. Results: A total of 132 patients were deemed eligible for our study with a mean age of 52. There was no statistically significant association between overall survival and disease-free survival with age and comorbidities apart from HIV. The median overall survival was 15 months and median disease-free survival for patients who completed radical treatment was 13 months. Overall survival and disease-free survival between presence and absence of hydronephrosis was not statistically significant. Conclusions: Hydronephrosis was not found to have a statistically significant impact on overall survival or disease-free survival. There remains a place for percutaneous nephrostomies in the acute setting and is preferred over ureteral stents in a resource-constrained setting. HIV was found to have an association with increased incidence of stage IIIB cervical cancer, as well as a negative prognostic factor for overall survival and disease-free survival.